Estudo da influência do preenchimento de alvéolos em lajes alveolares submetidas à força cortante - Pinheiro, Gregory Lee (Universidade Federal de São Carlos, 2014)
The use of precast elements has become crescent in Brazil, due to the need of haste during production as well as while assembling the structures. Bearing in mind a quick assembly and the competitive price for this kind of frame, precast elements have been growing and spreading in this field throughout the country. There is something special about demanding hollow core slabs, in virtue of their own low weight, in face of the empty spaces generated by the hollows and a better use of materials because of pretension technique, making it economically feasible. The National Technical Code ABNT NBR 9062, which deals with precast concrete structures, shows no more specific criteria as far as hollow core slabs are concerned, but on the other hand the 2011 review in force to ABNT NBR 14861 which covers precast hollow core slabs brings about relevant aspects such as the method used to check the capacity of shear strength on precast hollow core slabs, both with and without concrete structural cover, and furthermore with and without hollow fillings. Considering the reduced amount of national research on this topic, this study aims to develop and perform techniques in different ways of filling the hollows and the slabs and how they behave when exposed to shear strength tests. As a consequence to the manufacturing process of such type of slab and the hollow- filling method, failure in the idealized filling, in virtue of each material own behavior and inappropriate technique are commonly found.
Keywords: Lajes alveolares; Preenchimento de alvéolo; Concreto pré-fabricado; Ensaio de força cortante; Hollow core slab; Hollow core filling; Precast concrete; Testing; Shear force; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL